Reminiscence in Everyday Conversations: A Naturalistic Observation Study of Older Adults. (28th November 2017) - Demiray, Burcu; Mischler, Marianne; Martin, Mike
Abstract: Objectives: We examined older adults' social reminiscence behavior in everyday life, and the relation between reminiscence functions and well-being. Method: The sample included 2, 164 sound snippets that included speech from 45 healthy older adults. We examined reminiscence in daily conversations using the Electronically Activated Recorder. Across four days, we collected a random sample of about 280 sound files (30 seconds long) per participant. Participants' utterances were coded for whether they included reminiscence, for their functions and conversation partners. Participants completed mood and life satisfaction measures. Results: Participants reminisced in 5% of their utterances (range: 0%–29%). They reminisced in 40% of cases with friends, 32.8% with their partner and 8% with their children/relatives. Three reminiscence functions were observed: identity, teaching/informing, and conversation. Participants' reminiscence served the identity function while they were reminiscing with their partner and children. Participants reminisced to teach/inform while reminiscing with their children and strangers. Reminiscing for conversation occurred mainly with partner and friends. We found positive relations between life satisfaction and identity, teach/inform, and conversation functions. Mood had a negative relation with identity and teach/inform functions. Discussion: This is the first study to take a naturalistic observation approach to reminiscence and to build on self-report data.